Verbal Phrase Ellipsis in Xitsonga Language: A Linguistic Corpus-Based Approach - Molotja, Tsebe Wilfred; Maswanganyi, Khazamula N. (Universitas Jambi, Magister Program of English Education Department, 2026)
In literature, some sentences often omit words for dramatic effect, to signify a trailing thought, or to create pauses; sometimes omitting words to create a conversational dialogue. This study investigates gapping in the Xitsonga language, a type of verbal ellipsis. Judgmental sampling was used to select sources. The research was qualitative and descriptive in nature. Data were collected using the corpus method and analysed through content analysis, following the assumptions of ellipsis theory. Humans and/or animals were never involved as participants. The results reveal that gapping occurs in the Xitsonga language, in which elements are elided from a sentence without affecting its meaning. Verbal phrase units that are omitted could be recovered elsewhere within texts. Linguistic elements omitted may be realized from the verbal phrases and/or conjunctive sentences. The verbal phrase elements omitted from their positions do not change the sentence's meaning. They could be recovered from somewhere within the text environment.